Home / Expert Answers / Chemistry / given-the-ka-values-estimate-the-pka-value-of-each-of-the-following-acids-without-using-a-calculato-pa363

(Solved): Given the Ka values, estimate the pKa value of each of the following acids without using a calculato ...



Given the Ka values, estimate the pKa value of each of the following acids without using a calculator (that is, is it between 3 and 4, between 9 and 10, and so on?)

Nitrous acid \( \left(\mathrm{HNO}_{2}\right), K_{\mathrm{a}}=4.0 \times 10^{-4} \)
Express your answers as integers separate
Nitric acid \( \left(\mathrm{HNO}_{3}\right), K_{\mathrm{n}}=22 \)
Express your answers as integers separated by a comma.
bet
Bicarbonate \( \left(\mathrm{HCO}_{3}^{-}\right), K_{\mathrm{a}}=6.3 \times 10^{-11} \)
Express your answers as integers sepa
Hydrogen cyanide \( (\mathrm{HCN}), K_{\mathrm{a}}=7.9 \times 10^{-10} \)
Express your answers as integers separated by a com
Formic acid (HCOOH), \( K_{\mathrm{a}}=2.0 \times 10^{-4} \)
Express your answers as integers separated by a comma.
Nitrous acid \( \left(\mathrm{HNO}_{2}\right), K_{\mathrm{a}}=4.0 \times 10^{-4} \) Express your answers as integers separated by???a comma. Nitric acid \( \left(\mathrm{HNO}_{3}\right), K_{\mathrm{n}}=22 \) Express your answers as integers separated by a comma. between (1) Term 1: When using \( \log \) as a function, follow it with an argument in parentheses. No credit lost. Try again. Bicarbonate \( \left(\mathrm{HCO}_{3}^{-}\right), K_{\mathrm{a}}=6.3 \times 10^{-11} \) Express your answers as integers separated by a comma. Hydrogen cyanide \( (\mathrm{HCN}), K_{\mathrm{a}}=7.9 \times 10^{-10} \) Express your answers as integers separated by a comma. Formic acid (HCOOH), \( K_{\mathrm{a}}=2.0 \times 10^{-4} \) Express your answers as integers separated by a comma.


We have an Answer from Expert

View Expert Answer

Expert Answer


ESTIMATION OF pKa VALUES PART A:- Nitrous acid HNO2 ;Ka = 4.0*10-4 The general formula for calculating pKa values if Ka is given is pKa = -log(Ka) = -log(4.0*10-4 ) = -(log(10-4 ) + log 4) = -( -4*log10 +log4) = -(-4+ log4) = 4- log 4 Using
We have an Answer from Expert

Buy This Answer $5

Place Order

We Provide Services Across The Globe